An analysis of commercially recommended profiles for normobaric preacclimatization - Markus Tannheimer; Raimund Lechner (University of Applied Sciences in Tarnow, Poland, 2021)
Introduction: Normobaric hypoxic training (NHT) for preacclimatization at home has found its way into commercial expedition mountaineering. Portable NH-generators produce a normobaric hypoxic gas mixture that can be inhaled using breathing masks at rest or during exercise or it can be pumped into lightweight tents for sleeping. These devices can be rented from commercial companies. Materials and methods: Prior to an expedition to Manaslu (8163 m) NHT was used for preacclimatization over a period of 10 days. Our regimen involved a greater increase in sleeping altitude (10 nights to reach 5400 m) than recommended by the rental company (30 nights to reach 3900 m). Results: No incidents occurred during NHT. Our regimen induced sufficient acclimatization to Manaslu Base Camp (4900 m), as evidenced by the fact that none of the expedition members suffered from AMS although they reached base camp within 2 days from Kathmandu - by helicopter flight to 3500 m and a one day walk the next day. Eight days after leaving Kathmandu, camp III was reached at 6850 m. Conclusions: At natural altitudes above 2500 m an increase of sleeping altitude should not exceed 300-500 m per day. Below 2500 m, there are no restrictions. It is therefore unclear why the company recommends such a slow increase in sleeping altitude. In our opinion, it is not necessary for healthy persons to start with a sleeping altitude below 2500 m. In contrast to natural altitudes, NH exposure can be instantly stopped if symptoms occur. Therefore, it seems safe to expose healthy persons to more liberal normobarichypoxic conditions.